Genetic Mechanisms of Antimicrobial Non-Susceptibility to Novel Fluoroquinolone Delafloxacin Among Bulgarian Clinical Isolates of Streptococcus agalactiae - Vasil Boyanov; Alexandra Alexandrova; Raina Gergova (Current Issues in Molecular Biology, 2025)
Delafloxacin is one of the newest fluoroquinolones with a unique structure, determining better pharmacokinetic and pharmacodynamic properties, a better safety profile, and a broader spectrum of activity compared to older quinolones. We aimed to examine the susceptibility rates of delafloxacin, the genetic mechanisms contributing to resistance, and the serotype distribution in both invasive and non-invasive Streptococcus agalactiae strains. A total of 301 streptococcal strains were tested for minimal inhibitory concentration (MIC) to delafloxacin. All delafloxacin-resistant strains were subjected to serotyping, PCRs for quinolone-resistant genes, and sequence analysis for missense and silent mutations. Among the tested isolates, we found a 5.6% non-susceptibility rate to delafloxacin. The MICs ranged between 0.09 and 0.38 µg/mL, with a breakpoint for nonsusceptibility set as >0.03 µg/L, according to EUCAST criteria. All resistant isolates harboured missense mutations that led to amino acid substitutions in both GyrA (S81L) and ParC (S79F). Two common serotypes were determined among the resistant isolates: V (47.1%) and III (41.2%). Two strains were non-typable (11.7%). A statistical significance in the distribution of serotypes between delafloxacin-resistant and delafloxacin-susceptible strains was found. These findings highlight a concerning pattern of drug resistance developing prior to the introduction of a new medication, attributed to the extensive use of current antibiotics.